Pembiayaan Jaminan Kesehatan Nasional untuk Layanan Telemedicine di Indonesia, Taiwan, dan Korea Selatan - Rani Tiyas Budiyanti; Chriswardani Suryawati; Matsna Hanifah (Politeknik Negeri Jember, 2023)
The development of telemedicine technology in Indonesia is growing rapidly, especially during the Coronavirus Disease 2019 (COVID-19) pandemic. It can be the alternative solution to improve the quality of health services in the pandemic era without the patient and the health professional meet through offline. Several challenges arise in the application of telemedicine, one of them related to health financing. This study aims to identify potency of implementing national health insurance financing for telemedicine services in Indonesia. The research method was tradtional literature review with data obtained from journal articles indexed in the Google Scholar, Research Gate, PubMed, and Scopus databases that was done between January to February 2022. The keywords used in the article search were “Telemedicine”, “Universal Health Coverage”, “Telemedicine”, “Implementation